Exploring the Impact of Expertise, Clinical History, and Visual Search on Electrocardiogram Interpretation. (January 2014) - Wood, Greg; Batt, Jeremy; Appelboam, Andrew; Harris, Adrian; Wilson, Mark R.
Background: The primary aim of this study is to understand more about the perceptual-cognitive mechanisms underpinning the expert advantage in electrocardiogram (ECG) interpretation. While research has examined visual search processes in other aspects of medical decision making (e.g., radiology), this is the first study to apply the paradigm to ECG interpretation. The secondary aim is to explore the role that clinical history plays in influencing visual search behavior and diagnostic decision making. While clinical history may aid diagnostic decision making, it may also bias the visual search process.Methods: Ten final-year medical students and 10 consultant emergency medics were presented with 16 ECG traces (8 with clinical history that was not manipulated independently of case) while wearing eye tracking equipment. The ECGs represented common abnormalities encountered in emergency departments and were among those taught to final-year medical students. Participants were asked to make a diagnosis on each presented trace and report their level of diagnostic confidence.Results: Experts made significantly faster, more accurate, and more confident diagnoses, and this advantage was underpinned by differences in visual search behavior. Specifically, experts were significantly quicker at locating the leads of critical importance. Contrary to our hypothesis, clinical history had no significant effect on the readers' ability to detect the abnormality or make an accurate diagnosis.Conclusions: Accurate ECG interpretation appears dependent on the perceptual skill of pattern recognition and specifically the time to fixate the critical lead(s). Therefore, there is potential clinical utility in developing perceptual training programs to train novices to detect abnormalities more effectively.